The use of budgetary and financial information by politicians in parliament: a case study - Jorge, S. M.; Jesus, M.; Nogueira, S. P. (Journal of Public Budgeting, Accounting and Financial Management, 2019)
Purpose: The purpose of this paper is to research the use of accounting information by politicians. Based on the Portuguese Parliament setting, it seeks to understand how useful politicians consider this information to be, what type of budgetary and financial information they use, and for what purposes. Finally, the research also seeks to find out whether politicians resort to expert intermediaries or advisors help them in the use of this information. Design/methodology/approach: Following a qualitative and interpretative methodology, the study draws upon interviews with Members of Parliament in Portugal (and their technical advisors (TAs)) from all political parties, in particular the members of the Budget, Finance and Administrative Modernization Committee (COFMA) of the Parliament. Findings: Research shows that, due to the general lack of knowledge and the complexity of the accounting information, politicians in the Parliament do not use it frequently, only occasionally. To be better or worse informed for the debates and other activities depends on each Member of Parliament’s personal willingness to prepare oneself, notwithstanding some aggregated and previously analyzed information made available by official technical support units. Parliamentarians may also resort to TAs, who prepare the information at their request. Both intermediaries and TAs are deemed important to support parliamentarians’ understanding of more technical budgetary and financial issues. Practical implications: This paper shows that politicians acknowledge there is room for improving the role of information intermediaries and advisors, who would support them to better understand and use accounting information. Parliamentary groups incharge of hiring advisors, as well as accounting professionals, in Portugal and in other countries, must be aware of the very useful role accountants play in this process. Social implications: While allowing to understand whether and how politicians use accounting information, this research contributes to the process of public sector accounting reforms in Portugal, and at an international level, inasmuch as public sector accounting and reporting standards should better address these users’ information needs. Assuming that these reforms would foster more accurate, transparent and useful information for accountability and decision making, it is essential that politicians acknowledge and become real users of accounting information, in order to accomplish those objectives. Originality/value: This study contributes to the general knowledge of how politicians use accounting information. Academic studies so far have not gathered enough evidence about the type of accounting information that is actually important for politicians. This paper highlights that use of such information by politicians depends on individual skills and their willingness to receive the appropriate advice.